Industrial energy systems handbook - Williams, Albert (River Publishers series in energy engineering and systems, 2022)
Industrial Energy Systems Handbook is a supplementary reading resource for candidates undertaking the Association of Energy Engineers (AEE) Certified Industrial Energy Professional (CIEP) program.Understanding how the various industrial systems work is key to identifying savings opportunities. An overview is given of the global energy situation as at the time of publication which cements the necessity to improve energy intensive processes to become more optimized.Comprehension of opportunities to optimize an industrial energy system starts with the fundamentals of energy, electrical energy and thermal energy, and the importance of energy management systems and industrial energy audits.The main energy consuming systems in industry are covered such as steam, compressed air, motors, drives, fans, pumps, lighting, furnaces, heat exchange systems, and large scale cooling and industrial refrigeration. The instrumentation and control as well as toolkits available rounds off the handbook topics